(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Violence perpetrated against children and adolescents has been increasingly discussed at a global level, considering the various impacts that it provides at an individual, social and economic level. Objective: To identify studies about the impacts of domestic violence on social and health aspects of adolescents. Methods: This is a systematic review guiding by the question “What are the impacts of domestic violence on adolescents’ social and health aspects?”. The articles were selected in the databases MEDLINE, LILACS and BDENF. Results: This study included 22 articles published from 2002 to 2019, divided into three categories: impact on mental health, risk behaviors and involvement in situations of violence. Conclusion: It is concluded that adolescents who are victims of domestic violence have more difficulty in maintaining healthy social relationships, resulting in negative influences on their physical, psychological, sexual and social life.